SERA POOLED STABILITY AS A SGPT CONTROL MATERIAL WITH STORAGE TIME AND TEMPERATURE VARIATION - Lestari, Wuni Sri; Karwiti, Witi; Latifah, Aminahtun; Listiani, Yenni; Harianja, Sri Hartini (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Palembang, 2022)
To improve the quality of laboratory examination results, it is absolutely necessary to carry out quality assurance and these activities usually require control materials. The price of expensive commercial control materials is an obstacle to carrying out laboratory quality control. Efforts to maintain quality control are using pooled sera as control material. One of the examinations that is often done is the examination of SGPT (Serum Glutamic Pyruvate Transaminase) blood. The choice of SGPT parameter is expected to represent the type of enzyme assay. The purpose of this study was to determine the stability of pooled sera used as control material for SGPT examination with time and temperature variations. Methods: This research is an experimental study, which was carried out using a collection of serum found in the TLM Clinical Chemistry Laboratory of the Health Ministry of Health, Jambi. By using 2 treatments, the samples were stored at a temperature of 20-25oC and -5oC. Data analysis using ANOVA and coefficient of variation value. Results: The results showed a significant value (p-value) of SGPT of p = 0.008. A significant value (p-value) which is greater than the value of = 0.05, indicates that there is an effect of storage time and temperature variations. Conclusion : There is a significant effect of storage time and temperature variation of pooled sera control material on the stability of SGPT examination.